2019
DOI: 10.30848/pjb2019-3(16)
|View full text |Cite
|
Sign up to set email alerts
|

Identification of allelic variants of Xgwm261 locus for Rht8 dwarfing gene in Pakistani wheat genetic resource

Abstract: Semi dwarfing wheat gene (Rht8) is among the important Green Revolution genes to increase productivity by modifying plant stature. Plant height is among one of the important constituent of plant architecture that determines the stability, harvest index and yield of crop plants. Strong linkage of Xgwm261, a wheat microsatellite marker with the dwarfing gene (Rht8) resulting in reduced height makes it well known marker among the breeders. Using this functional SSR marker, Pakistani wheat varieties and land races… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The results from the investigations show that the researches on the genetics of the qualitative indices are important for the improvement of the breeding process since these results allow determining the relationships between the composition of the storage endosperm proteins and the technological properties of grain. (Tabasum et al, 2011;Carter et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The results from the investigations show that the researches on the genetics of the qualitative indices are important for the improvement of the breeding process since these results allow determining the relationships between the composition of the storage endosperm proteins and the technological properties of grain. (Tabasum et al, 2011;Carter et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that higher irradiation led to lower plant height, stem diameter, branch and leaf numbers. The research of [50] and [51] approved that each individual had different genotype response to gamma irradiation.…”
Section: Morphology Of Vegetative Growth In Mutant Plantsmentioning
confidence: 99%